Pandangan Masyarakat Desa terhadap Dinamika Politik Pasca Pemilihan Gubernur Aceh 2017 - Teuku Muzaffarsyah; Bobby Rahman; Zulhilmi Zulhilmi; Eny Dameria; Mahdi Mahdi (Asia-Pacific Journal of Public Policy, 2021)
This study aims to understand and look closely political beliefs of the villagers in the North Aceh Regency after the 2017 gubernatorial election. A qualitative method was employed and the data were generated from written or spoken words from people and their behaviors. Observations and personal in-depth interviews were conducted to collect rigorous information from the informants at a village in the North Aceh district, Indonesia. The finding reported that the behavior of the community in responding to the political dynamics after the election for Governor of Aceh in 2017 continued to behave according to the conditions of a political party that they supported to achieve particular goals. Their responses were increasingly rational and willing to accept differences and participated based on shared awareness to build the nation so that they could feel the welfare of living in peace. The finding implies that societies now can no longer be lied to with irrational promises from the politicians during the political campaign. People are now becoming intelligent and rational in the political election because they have learned lessons from numerous political blunders in the past.